Strategies for Avoiding Complications with Vascularized Bone Flaps in Head and Neck Microvascular Reconstruction - Mitchell, David A. (Thieme Medical Publishers, 2008)
Effective osseous reconstruction of the head and neck after congenital, traumatic, and particularly ablative oncologic procedures is a relatively recent innovation. Whereas pioneers led with individual donor sites, it is only in the past 20 years that most centers have developed teams comfortable with use of the four common donor sites for free flaps: iliac crest, fibula, radius, and scapula. Calvarium, though much less frequently used, is a useful donor site for specific reconstructive challenges. Less commonly used sites such as femur, humerus, and rib have not proved universally reliable. This article aims to illustrate some refinements and pitfalls in vascularized osseous reconstruction of the head and neck using the well-recognized flaps, including calvarium, in a variety of pathologic conditions, recipient-site defects, and comorbidities. Strategies for error avoidance will be emphasized. The authors hope that this will support the concept of a reconstructive “toolbox” for this complex area.